2006
DOI: 10.1164/rccm.200604-519oc
|View full text |Cite
|
Sign up to set email alerts
|

Health Effects of the 2003 Southern California Wildfires on Children

Abstract: Rationale:In late October 2003, Southern California wildfires burned more than 3,000 km 2 . The wildfires produced heavy smoke that affected several communities participating in the University of Southern California Children's Health Study (CHS). Objectives: To study the acute effects of fire smoke on the health of CHS participants. Methods: A questionnaire was used to assess smoke exposure and occurrence of symptoms among CHS high-school students (n ϭ 873; age, 17-18 yr) and elementary-school children (n ϭ 5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
190
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(200 citation statements)
references
References 25 publications
2
190
0
3
Order By: Relevance
“…Thus we defined 6-8 July 2002 as our haze period, when air pollution was also at its highest and compared it to a control non-haze period, corresponding to the same days of the preceding week (29,30 June and 1 July 2002). We chose not to include the same days in the following week as part of the control because of potential persisting effects in the post-haze period [19] The same days of the week were used in this fashion to minimize potential time-varying confounding effects, such as might be expected for weekday versus weekend.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus we defined 6-8 July 2002 as our haze period, when air pollution was also at its highest and compared it to a control non-haze period, corresponding to the same days of the preceding week (29,30 June and 1 July 2002). We chose not to include the same days in the following week as part of the control because of potential persisting effects in the post-haze period [19] The same days of the week were used in this fashion to minimize potential time-varying confounding effects, such as might be expected for weekday versus weekend.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of this increased pollution on the health of local populations has been well documented [9,11,13,17,29,30,[85][86][87]. For example, Duclos et al showed a 40% and 30% increase in number of local emergency room visits for asthma and COPD respectively, during 1987 forest fires in northern California [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wildfire emissions themselves are harmful to human health, but are exacerbated within urban pollution (Kunzli et al, 2006) and are difficult to quantify (McKeen et al, 2002). Singh et al (2012) outlined some of the current shortcomings in the Community Multiscale Air Quality (CMAQ) model associated with wildfire smoke.…”
Section: Introductionmentioning
confidence: 99%